COMPENSATION OF MORAL DAMAGE IN PRACTICE THE EUROPEAN COURT OF HUMAN RIGHTS - M. F. BAGLARIDU (Московский журнал международного права)
The article is focused on particularities of approach of the European Court of Human Rights to consideration of validity of claims for compensation of moral damage to individuals. Within the framework of this article the author also concerns approach of the European Court of Human Rights to assessment of similar claims on compensation of moral damage to legal entities. Particularly, the author conducts analysis of approach used by the European Court of Human Rights in respect of definition of ‘moral damage’, methods and criteria of assessment of scope of damage subject to compensation, as well as definition of persons entitled to compensation of moral damage in its case consideration practice.Moreover, for the purpose of comparative analysis the author concerns in this article law enforcement problems and deficiencies existing in the domestic legal regulation of the institute of moral damage compensation to individuals and – partly – to legal entities.